Pesquisa de oocistos de Isospora spp. em passeriformes criados em cativeiro - Silva, Deuvânia Carvalho Da [UNESP]; Homem, Camila Guariz [UNESP]; Nakamura, Alex Akira [UNESP]; Silva, Valéria Cristina Da [UNESP]; Meireles, Marcelo Vasconcelos [UNESP] (Universidade Federal de Goiás, 2014)
This study aimed to research the long-term shedding of Isospora spp. oocysts in several species of passerines naturally infected and kept in captivity. Two hundred and eighty-nine fecal samples were collected from two flocks with previous diagnosis of isosporosis, in which several adult passerine species were raised. Samples were collected individually, monthly, for 13 months, purified in Sheather's sugar solution and examined using microscopy. Of the 289 samples, 159 (55.02%) were positive for Isospora spp. oocysts and 130 (44.98%) were negative. Most of the birds analyzed shed oocysts in small quantity (score 1), intermittently and for a long period. Despite the occurrence of Isospora infection, the birds that were analysed showed no clinical isosporosis. The results of this research provide data for the control of isosporosis in passerines raised in captivity. The decisions about performing prophylactic or curative treatment, as well as decisions related to hygiene and sanitary measures must take into account not only the presence of the parasite in feces, but also the intensity of oocysts shedding, as well as evaluation of sanitary and nutritional management and the presence of clinical signs and/or mortality.

O presente estudo teve como objetivo pesquisar, em longo prazo, a presença de oocistos de Isospora spp. em várias espécies de passeriformes, naturalmente infectadas, criadas em cativeiro. Foram colhidas 289 amostras em dois criatórios de passeriformes, onde houve comprovação prévia de infecção por Isospora, nos quais havia alojamento de várias espécies de passeriformes adultos. As amostras foram colhidas de forma individual, com periodicidade mensal, por 13 meses, purificadas em solução de Sheather e examinadas por microscopia. Das 289 amostras, 159 (55,02%) apresentaram positividade para oocistos de Isospora e 130 (44,98%) foram negativas. Na maioria das aves analisadas foi observada eliminação de oocistos, em pequena quantidade, intermitente e por período prolongado. Apesar de todas as aves apresentarem oocistos de Isospora nas fezes pelo menos uma vez, em um período de 13 meses, as aves não apresentaram isosporose clínica. Os resultados observados neste experimento fornecem dados para o controle da isosporose em passeriformes criados em cativeiro. As decisões sobre a realização de tratamento profilático ou curativo, assim como sobre medidas higiênico-sanitárias a serem adotadas devem levar em consideração não somente a presença de parasito em fezes, mas também a intensidade de eliminação de oocistos, ssim como a avaliação do manejo higiênico sanitário e nutricional e a presença de sinais clínicos e/ou de mortalidade.
Screening for Isospora spp. oocysts in passeriformes raised in captivity
Keywords: Birds; Fecal samples; ISospora spp.; Oocysts; Amostras de fezes; Aves; ISospora spp.; Oocistos